Purification of Waste Water Containing Chlorhexidine Digluconate Using Nanoporous Carbons Obtained from Different Raw Materials - Bilyana Petrova; Ivanka Stoycheva; Boyko Tsyntsarski; Angelina Kosateva; Nartzislav Petrov; Pavlina Dolashka (Chemistry)
Activated carbons were obtained from three types of raw materials from the canning industry: peach, plum, and olive stones. The chemical composition and texture of the precursors and the physicochemical properties of the obtained carbons were analyzed. It was found that under the same conditions of preparation, the properties of the raw materials significantly affect the parameters of the activated carbons. The obtained carbons were oxidized with 12% nitric acid to form a larger amount of acidic oxygen-containing groups on their surface. The porous texture, the size, and the chemical nature of the surface of the activated carbons were analyzed. The adsorption capacity of the obtained activated carbons towards chlorhexidine gluconate contained in mouthwash was determined. It was found that the three carbons have a significant adsorption capacity towards chlorhexidine gluconate: 189.1 mg/g for carbon from peach stones, 189.1 mg/g for carbon from plum stones, and 156.7 mg/g for carbon from olive stones, respectively. It has been determined that the adsorption of chlorhexidine gluconate on the surface of the obtained activated carbons obeys the Langmuir model. It has been established that the adsorption capacity of the obtained activated carbons is influenced by their porous texture, size, and chemical nature of the surface.